Proposed Business Model for Tourism Integrated Service of PT Pojok Celebes Mandiri (Pointer) to Enter The Malaysian Market Using Lean Startup Approach - Wulandari, Eliandri Shintani; Aprianingsih, Atik (The Indonesian Journal of Business Administration, 2015)
Abstract.The Indonesian tourism industry is growing rapidly followed by increased competition in this industry sector and the interests of both local and foreign tourists to Indonesia tourism destination. The development of tourism industry needs to be supported by the readiness of infrastructure, including Information and Communications Technology (ICT) in Indonesia. Telkom as the biggest provider of ICT in Indonesia need to have an important role and participate in this development program of tourism business in Indonesia. By acquiring Pointer as a subsidiary company, which is a company that provide an online booking system for airline ticket through the Hi-Indonesia, where the value proposition is in their integration system owned as integrated solutions that make the flight booking process becomes more reliable and safe. In addition, Pointer also developed the www.pointer.co.id portal as a tourism exchange provider who has the ability to create the connection between suppliers of services such as airline companies through the Central Distribution System (CRS) and Online or Offline Travel Agents for B2B segmentation. In accordance with the Pointerâ€™s Â roadmap in 2015 to do the international expansion, Pointers need to conduct a study to determine the appropriate market according to market requirements in the targeted country. In this study, Pointer is pointing Malaysia as their first stage of international expansion.Root cause needs to be determined, Pointer needs to know the current market situation and also their capability to find the appropriate way Â to find the product and market fit. The external analysis, Internal Analysis and SWOT analysis are needed to be conducted. In this process, Pointer also uses the Lean Startup approach as a tool to find the suitable market for their product. The lean startup approach helps Pointer to find the real capture of customer behavior, their preferences and painful problem that may occur regarding to their activities in preparing their trip to Indonesia and the customer has the important role and always engage in all process of this Lean Strartup approach. Pointer needs to gather many insights about their customer experience of using the existing facilities of airline booking, ticket search engine for the Indonesian domestic route. Through the Lean Startup approach, Pointer can get the root cause of this painful problem of real customer that need to be solved by Pointer. Pointer can also determine the minimum viable product (MVP) to be developed to become the â€œready to sellâ€ in Malaysia.Business solution for defining business issue emphasizes on a proposed new business model that appropriate and fit be launched in Malaysia. Pointer can determine the suitable market segmentation as their early adopter customer who will adopt this proposed product to support their related tourism activities and business.So that the expected output of this Lean Startup approach can give a sustainable competitive business growth and provide a new revenue stream for Telin and related parties regarding to this the tourism industry.